A BIBLIOMETRIC STUDY ON MHEALTH AND ARTIFICIAL INTELLIGENCE - Priyadarsini.P.G; K. Poorna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mobile health is defined as medical and public health practices supported with the help of mobile devices. In India, there is a huge growth in mobile phone usage and Internet usage, which can be beneficial to expand mobile health usage. It has several advantages, including minimizing the spread of infection, saving time, and being very convenient to use. mHealth usability and personalization should be considered while updating or developing an mHealth app, as they are very important features. There’s a pause in the association between sufficient income and higher usability scores. Among emphasis app users in Egypt and Saudi Arabia (Arafa et al., 2022). mHealth apps, or mobile health apps, are the software used in mobile devices such as smartphones or tablets to provide health-related services, information, and support. These apps can cover a wide range of health-related functions, such as physical tracking, monitoring the person’s health condition in remote areas, and providing educational resources, which can be useful for patients who cannot come to hospitals and stay for a long time. These health apps can help facilitate health records and promote healthy lifestyle behaviours among patients (Haggag et al., 2022). The mHealth apps are mainly used for mental health, chronic disease management, physical fitness, and weight loss, as they are a cost-effective and time-saving method. These apps can be customized according to the air-specific region, considering cultural differences and language preferences, which can be beneficial for mHealth app users. These apps can improve lifestyles, healthcare delivery systems to address the burden of diseases, and much more (Figueiredo & Chunkhare, 2021). Mobile health is a dominant concept closely related to artificial intelligence and genomics. In today’s world, artificial intelligence and machine learning are used in health to combine with ICT and other technologies to solve problems that are related to patients and consumers (Fatehi et al., 2020).